Information System Inventory Of Office Writing Equipment At PT Lion Super Indo Majapahit Semarang Branch - Herlina Dini Damayanti; Dani Sasmoko; Andik Prakasa Hadi (Lembaga Pengembangan Kinerja Dosen, 2023)
A computerized system is the use of a computer as a tool in data processing activities that are carried out manually. Inventory is all kinds of company goods that are available to be processed in the production process or sold. PT LION SUPER INDO is a company operating in the trading sector. PT LION SUPER INDO has 151 branches, one of which is PT Lion Super Indo Majapahit branch. The problem that often arises is the management of office stationery, the availability of which is not maintained, because there are obstacles in the process of using office stationery activities which are recorded manually. This can result in excess, shortage, or running out of Office Stationery. The method used is through the process of observation and interviews, namely by observing the management of office stationery supplies and obtaining the data the author needs in implementing the system. Implementation takes the form of the final result achieved, namely the formation of an information system based on visual basic programming, because by using this system you will be able to process data quickly and accurately. From this research it can be concluded that with the design of an office stationery supply information system at PT LION SUPER INDO Majapahit Branch based on Visual Basic, it can provide accurate information services. If there is an order transaction, the office stationery data can also be added to the store warehouse data automatically. Likewise, if there is a usage transaction, it will automatically reduce the stock in the store's warehouse data, so that the office stationery data will match the physical goods. And makes it easier for leaders to make office stationery decisions in ordering in each period.